2014
DOI: 10.3389/fonc.2014.00001
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy and the Tumor Stroma: The Importance of Dose and Fractionation

Abstract: Ionizing radiation is a non-specific but highly effective way to kill malignant cells. However, tumor recurrence sustained by a minor fraction of surviving tumor cells is a commonplace phenomenon caused by the activation of both cancer cell intrinsic resistance mechanisms, and also extrinsic intermediaries of therapy resistance, represented by non-malignant cells and structural components of the tumor stroma. The improved accuracy offered by advanced radiotherapy (RT)-technology permits reduced volume of healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
266
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(274 citation statements)
references
References 162 publications
(199 reference statements)
6
266
1
Order By: Relevance
“…To decrease the side effects, low-dose irradiation (LDI) has been explored. Intriguingly, despite its very poor tumor cell-killing effect, LDI is actually able to improve antitumor immunity through modulating macrophages, recruiting T cells to tumor sites and other ways, [19][20] raising a possibility of LDI enhancing the anti-TRC effect of drug-MPs followed by a better modulation of antitumor immune microenvironments. This study demonstrates that the combination of drug-packaging MPs and LDI effectively reverses macrophage polarization from tumor-promoting to tumor-inhibiting through disrupting TRCs, providing a new strategy for tumor immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…To decrease the side effects, low-dose irradiation (LDI) has been explored. Intriguingly, despite its very poor tumor cell-killing effect, LDI is actually able to improve antitumor immunity through modulating macrophages, recruiting T cells to tumor sites and other ways, [19][20] raising a possibility of LDI enhancing the anti-TRC effect of drug-MPs followed by a better modulation of antitumor immune microenvironments. This study demonstrates that the combination of drug-packaging MPs and LDI effectively reverses macrophage polarization from tumor-promoting to tumor-inhibiting through disrupting TRCs, providing a new strategy for tumor immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent SBRT studies showed local control rates and toxicity profiles were comparable to the conventional dose regimen of 2 Gy per fraction (2 Gy/Fx) 2, 3. It has been reported that with a prescription dose of 7.25 Gy/Fx or higher in SBRT treatment planning, margins are usually 5 mm or smaller to spare the surrounding organs at risk such as rectum, urethra, and bladder 1.…”
Section: Introductionmentioning
confidence: 99%
“…Through an active humoral and physical cross talk ME can determine invasion, ability to metastasize, immunogenicity of cancer and response to anticancer therapies including radiation therapy (RT). The effects of radiotherapy reported on tumor cells are conflicting, and the general belief on immunity is that different microenvironments and diverse delivery modalities may induce activation or inhibition of immune response and the size of fraction is one of the variables involved in such a dualism [1][2][3].…”
Section: Introductionmentioning
confidence: 99%